Seizing the serendipitous moments: Coincidental creative processes in media work. (November 2019) - Malmelin, Nando; Virta, Sari
This article discusses the phenomenon of serendipity in media work and in media organizations. Based on an empirical analysis of diary material, we identify and elaborate three types of serendipitous processes in creative work, that is, serendipitous, semi-serendipitous and antiserendipitous processes. In addition, we discuss the role of lucky incidents and human capabilities in serendipity, and consider their value to creative processes in media organizations. We argue that conceptual frameworks and theories of serendipity are useful in identifying, evaluating and harnessing unpredicted and accidental creative incidents and processes. The article shows that serendipity offers valuable conceptualizations and insights for scholars and practitioners alike in the context of the rapidly changing media industry and media work.